Narratives of Ruins and Renewal: Trauma and Recovery in selected Palestinian Novels - Mamona Yasmin Khan; Huda Waasfa (Research Journal of Psychology, 2025)
Palestinian literature is testament to the enduring human spirit, weaving together stories of love, loss and resilience in the face of trauma and ongoing conflict. The present study aims to explore the different dimensions of trauma along with the process of recovery in selected Palestinian fiction The Blue Between Sky and Water (2015) and Against the Loveless World (2020) penned by Susan Abulhawa. It yearns to elaborate that personal trauma when exposed to long period of time especially, at time of war or captivity does not only remain to one person rather extends at communal level by using the theoratical lens of Judith Herman (2015). Therefore, trauma along with its various episodes of remembrance and reconnection proceeds the process of restoration. The catastrophe of Al-Nakba (1948) forced huge masses of Palestinians, the real residents of land to move from their own homeland, resulting in widespread destruction, massacre, and enduring psychological and social turmoil at both personal and collective levels. This study profoundly focuses on trauma and road to resilience to recuperate the voices of the voiceless or silenced victims.